Effect of add on therapy of SGLT 2 inhibitors on glycaemic parameters - Shanmuganandam, Subashini; M. J., Manjula (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Glycaemic control in type 2 diabetes mellitus can be difficult to attain, even with a combination of multiple oral agents as well as Insulin. SGLT2 inhibitors are potential novel agents inhibits the sodium glucose co transporters operated in the kidney tubules independent of the action on insulin resistance or secretion. This study aimed to evaluate the effect on the mean reduction of HbA1c levels. Also, to evaluate the effect of gliflozins on the mean reduction of FBS and PPBS values at the end of 3rd and 6th months and to find out the ADR profile over 6 months. Methods: Prospective observational study conducted on the patients with type 2 diabetes mellitus with HbA1c >7% not controlled on metformin in the outpatient over a period of 15 months. An initial visit and thereafter follow up visits at 3rd and 6th month. HbA1c, FBS and PPBS was noted. ADR profile was also noted. Results: Significant mean reduction in the glycemic parameters among 90% study population with 0.5% reduction in mean HbA1c from the baseline. Also, the reduction in FBS and PPBS were statistically significant by 3rd month of the treatment. Incidence of genital itching was more compared with conventional drugs. Hypotension and polydipsia were rare. Conclusions: SGLT 2 inhibitors are found to be a promising new category of antidiabetic medications with better control of FBS, PPBS and HbA1c.